Understanding the relationship between green restaurant certification programs and a green restaurant image: the case of TripAdvisor reviews. Issue 6 (24th July 2020) - Park, Eunhye (Olivia); Kim, Woo-Hyuk; Kwon, Junehee
Abstract : Purpose: The study aims to investigate the adoption of green certification programs by restaurants. More specifically, this study has three objectives: to examine the relationships between green certification program scores and customers' perceptions, duration of green certification and green brand image and food-focused green practices and green brand image. Design/methodology/approach: The authors collected 25, 098 TripAdvisor reviews, along with associated patron demographics, for 70 green certified restaurants. To investigate the hypotheses, the authors first used structural topic modeling to discover latent themes relevant to green restaurant practices. Thereafter, the authors used factorial Multivariate analysis of covariance (MANCOVA) to examine the association between formal certification participation and customers' green perceptions. Findings: The results showed that customers were more likely to perceive a green restaurant image after visiting green certified restaurants with higher certification ratings and green certification periods of longer duration. Practical implications: The current study contributes to the literature in several ways. First, this study uses post-visit online reviews written by customers of certified green restaurants to understand customers' natural responses more precisely. Second, the study captures the degree of green commitment by applying information about formal certification programs, where other studies have relied on hypothetical scenarios or survey questions to examine the impact of green attributes on customer perceptions. Originality/value: To the best of authors' knowledge, this is the first study to investigate the adoption of green certification programs by restaurants empirically with data drawn from actual user-generated content (i.e. TripAdvisor).